A new mount with moving-magnet type electromagnetic actuator for naval shipboard equipment - Yun-Ho Shin (International Journal of Naval Architecture and Ocean Engineering, 2015)
This study is proposed a new hybrid mount having a moving-magnet type electromagnetic actuator to reduce the vibration transmitted from naval shipboard equipment to the structure of the ship 's hull. Optimal design specifications are determined through experimental analysis. The detailed design of the hybrid mount is determined through several design steps with electromagnetic numerical analysis using Maxwell Software(S/W). The hybrid mount that combines a rubber mount and an electromagnetic actuator has a fail-safe function for shock resistance. The mount is fabricated and tested using a universal testing machine to evaluate the design specifications. Finally, numerical simulation of the hybrid mount is performed to confirm control performance and applicability.